Severe community-acquired pneumonia: Characteristics and prognostic factors in ventilated and non-ventilated patients - Ferrer, Miquel (PLoS One, 2018)
BACKGROUND: Patients with severe community-acquired pneumonia (SCAP) and life-threatening acute respiratory failure may require invasive mechanical ventilation (IMV). Since use of IMV is often associated with significant morbidity and mortality, we assessed whether patients invasively ventilated would represent a target population for interventions aimed at reducing mortality of SCAP. METHODS: We prospectively recruited consecutive patients with SCAP for 12 years. We assessed the characteristics and outcomes of patients invasively ventilated at presentation of pneumonia, compared with those without IMV, and determined the influence of risks factors on mortality with a multivariate weighted logistic regression using a propensity score. RESULTS: Among 3,719 patients hospitalized with CAP, 664 (18%) had criteria for SCAP, and 154 (23%) received IMV at presentation of pneumonia; 198 (30%) presented with septic shock. In 370 (56%) cases SCAP was diagnosed based solely on the presence of 3 or more IDSA/ATS minor criteria. Streptococcus pneumoniae was the main pathogen in both groups. The 30-day mortality was higher in the IMV, compared to non-intubated patients (51, 33%, vs. 94, 18% respectively, p<0·001), and higher than that predicted by APACHE-II score (26%). IMV independently predicted 30-day mortality in multivariate analysis (adjusted odds-ratio 3·54, 95% confidence interval 1·45–8·37, p = 0·006). Other independent predictors of mortality were septic shock, worse hypoxemia and increased serum potassium. CONCLUSION: Invasive mechanical ventilation independently predicted 30-day mortality in patients with SCAP. Patients invasively ventilated should be considered a different population with higher mortality for future clinical trials on new interventions addressed to improve mortality of SCAP.